Pallister-Killian syndrome: A case with sensorineural hearing loss - ÇİPRUT, AYŞE AYÇA (My University, 2006)
Pallister-Killian syndrome (PKS) is a rare disorder caused by tetrasomy 12p mosaicism. Pallister-Killian syndrome (PKS) is characterized by multiple congenital anomalies including pigmentary skin changes, mental retardation, and the mosaic presence of a tissue-limited isochromosome 12p [i(12p)]. Hearing loss is not reported very often in PKS patients. The purpose of the study is to present a Pallister-Killian syndrome patient with severe sensorineural hearing loss. Bilateral severe sensorineural hearing loss was diagnosed in a child of 28-month old with PKS. The child was fitted with hearing aids and began to receive auditory habilitation. The child benefited from the amplification. Hearing screening is recommended for children with multiple anomalies including PKS in order to prevent the harmful effects of the hearing loss. © 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: Mosaicism; Pallister-Killian; Sensorineural hearing loss; Tetrasomy 12p